Selectable Implant Removal Methods due to Mechanical and Biological Failures - Jong-Bin Lee (Case Reports in Dentistry)
Dental implant has been restoring the function and esthetics lost from missing tooth. However, biomechanical implant complications are the major cause of failing implants. Therefore, implant removal is one of the indispensable dental treatments. The 70-year-old male and 66-year-old female who had discomfort on posterior implants region came to Department of Periodontology. Conventional method using trephine bur and the new, nontraumatic method using a fixture removal kit were used for implant removal, respectively. Two different methods are commonly used for implant removal. Each has advantages and disadvantages; thus, the applied surgical method must consider a patient’s intraoral condition, posttreatment plan, and the level of surgeon’s skill and experience. In conclusion, strategically executing the most optimal implant removal method plays a pivotal role in maximizing the success rate of implant reinstallation that follows afterwards.